2009
DOI: 10.1080/09518390902915421
|View full text |Cite
|
Sign up to set email alerts
|

Seeing red: poetry and metaphor as responses to representational challenges in critical narrative research

Abstract: Research with young people who 'do not fit the mould' requires innovative and unconventional methods, but what are the implications of such methods for scholarly representation? This paper reports on the development of such a method with students diagnosed Attention Deficit Hyperactivity Disorder and offers one view of the borderland spaces and tensions between critical theory and narrative inquiry. In particular, the paper defines the methodology that underpins the 'critical cover narratives' method, describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Stigma toward pupils who display symptoms of ADHD may be common in schools and findings suggest this is likely to influence how well interventions work (Cooper & Shea, 1998; Hjörne, 2006; Ljusberg, 2011b; Prosser, 2006). Stigma acts as a protective device for existing social practice (Thornicroft, 2006), and therefore may be a barrier to change in addition to marginalizing the pupil, and possibly the pupils’ family (Carpenter & Austin, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stigma toward pupils who display symptoms of ADHD may be common in schools and findings suggest this is likely to influence how well interventions work (Cooper & Shea, 1998; Hjörne, 2006; Ljusberg, 2011b; Prosser, 2006). Stigma acts as a protective device for existing social practice (Thornicroft, 2006), and therefore may be a barrier to change in addition to marginalizing the pupil, and possibly the pupils’ family (Carpenter & Austin, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The purchase of interventions, training for teachers about ADHD, and time available for teachers to implement classroom interventions and/or collaborate with colleagues and parents may receive lower priority than academic considerations for the majority of pupils (Hong, 2008). Finally, studies suggested that pupils and parents often held the least amount of power in the school setting, as their treatment preferences were rarely acted on (Hibbitts, 2010; Malacrida, 2001; Prosser, 2006; Watson, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Narrative analysis has been suggested as one means that writers might better engage, interest and really move readers, for example, through the use of stories (Dowling, 2012;Prosser, 2009;Richardson & Adams St Pierre, 2005). Some time ago, Sparkes (2002) mapped out a variety of different ways in which research in PE and sport might be differently constructed and written to offer a challenge to the hegemony of the so-called "gold standard" of the realist, or scientific, tale.…”
Section: Narrative Constructionmentioning
confidence: 99%